2020
DOI: 10.1371/journal.pone.0227054
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein(a) plasma levels are not associated with survival after acute coronary syndromes: An observational cohort study

Abstract: Background Lipoprotein(a) [Lp(a)] is associated with coronary artery disease in population studies, however studies on its predictive value in patients with cardiovascular disease, in particular after acute coronary syndromes (ACS), are conflicting. The aim of this study was to investigate whether Lp(a) is associated with survival after ACS. Methods and results We analyzed Lp(a) measurement in 1,245 patients who underwent coronary angiography for ACS. The median follow-up for cardiovascular and all-cause morta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 24 publications
0
16
0
1
Order By: Relevance
“…We did not study Lp(a) genotypes, but other data suggest that Lp(a) mass or molar concentrations are better predictors of CVD risk [37]. Lp(a) levels may be lowered during the acute periods of AMI [38]. Despite this, the significant statistical associations that we found are supportive of Lp(a) as an important cardiovascular risk factor.…”
Section: Tablementioning
confidence: 59%
“…We did not study Lp(a) genotypes, but other data suggest that Lp(a) mass or molar concentrations are better predictors of CVD risk [37]. Lp(a) levels may be lowered during the acute periods of AMI [38]. Despite this, the significant statistical associations that we found are supportive of Lp(a) as an important cardiovascular risk factor.…”
Section: Tablementioning
confidence: 59%
“…The CV risk of elevated Lp(a) still remains an open question [ 19 ], in particular because of the unsettled definition of levels requiring treatment. Among the general population, Lp(a) concentrations have a more than 1000-fold interindividual range”, with a prevalence of 35% for values > 30 mg/dL, 20% for values > 60 mg/dL, 10% for values > 90 mg/dL, 5% for values > 116 mg/dL and 1% for values >180 mg/dL [ 20 ].…”
Section: Introduction—an Overviewmentioning
confidence: 99%
“…Three recent studies have shown that patients who underwent PCI or coronary artery bypass grafting with high Lp(a) had a worse mortality (40)(41)(42). Conversely, another study of 1,245 patients with acute coronary syndrome stratified into four groups according to the quartile of Lp(a) showed that Lp(a) is not associated with long-term mortality (43). In our study, high Lp(a) (>19.1 mg/dL) was strongly related to the long-term prognosis in the total population and in subgroup analyses, and a Cox regression analysis further revealed that Lp(a) is an indicator of all-cause mortality even after adjusting for risk factors.…”
Section: Discussionmentioning
confidence: 99%